2010
DOI: 10.1590/s1983-40632010000400015
|View full text |Cite
|
Sign up to set email alerts
|

Arranjo espacial, densidade e época de semeadura no acúmulo de matéria seca e nutrientes de três adubos verdes

Abstract: Objetivou-se avaliar o efeito de densidades de semeadura, arranjos espaciais e épocas de semeadura no acúmulo de matéria seca e nutrientes de Crotalaria juncea, Mucuna deeringiana e Cajanus cajan, em Pariquera-Açu, Vale do Ribeira (SP). Três experimentos foram conduzidos: 1) densidade de semeadura x adubos verdes, 2) arranjo espacial x adubos verdes e 3) época de semeadura x adubos verdes. O delineamento experimental adotado foi o de blocos casualizados, com quatro repetições, sendo os primeiros experimentos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
6
1
3
Order By: Relevance
“…Crotalaria effectiveness as a green manure essentially depends on plant biomass production under local conditions (WUTKE et al, 1993). Lima et al (2010) evaluated plant spatial arrangement, density and sowing time for three green manures; they observed that regardless of the sowing density, crotalaria was the most efficient species in dry biomass accumulation. The same authors noted that the largest dry matter accumulations occurred at the lowest density (500,000 plants/ha), registering yields of 16 t.ha -1 dry weight.…”
Section: Resultsmentioning
confidence: 99%
“…Crotalaria effectiveness as a green manure essentially depends on plant biomass production under local conditions (WUTKE et al, 1993). Lima et al (2010) evaluated plant spatial arrangement, density and sowing time for three green manures; they observed that regardless of the sowing density, crotalaria was the most efficient species in dry biomass accumulation. The same authors noted that the largest dry matter accumulations occurred at the lowest density (500,000 plants/ha), registering yields of 16 t.ha -1 dry weight.…”
Section: Resultsmentioning
confidence: 99%
“…Produtividades relativamente baixas para essas espécies, quando semeadas na mesma época na região do Cerrado, também são relatadas em outros trabalhos (Burle et al, 1999;Carvalho et al, 2004;Sodré Filho et al, 2004;Torres et al, 2005;Carvalho et al, 2008). No entanto, produtividades duas a três vezes superiores de matéria seca são comumente obtidas com o cultivo dessas espécies no início ou mesmo no final da estação chuvosa, com precipitações excepcionalmente mais elevadas e melhor distribuição de chuvas (Carsky et al, 1990;Boer et al, 2007;Lima et al, 2010;Marcelo et al, 2012).…”
Section: Resultsunclassified
“…Caatinga, Mossoró, v. 35, n. 1, p. 14 -25, jan. -mar., 2022 20 SOARES;MIRANDA, 2016;LIMA et al, 2010;CALVO et al, 2010). The higher value of C found in the species CJ, both in year 1 and in year 2, is related to its rapid initial growth in the first 40 days after sowing -DAS (TEODORO et al, 2011).…”
Section: Resultsmentioning
confidence: 93%